Demographics, psychiatric comorbidities, and hospital outcomes across eating disorder types in adolescents and youth: insights from US hospitals data - Jaka, Sanobar; Pokhrel, Sandesh; Patel, Archna; Sejdiu, Albulena; Taneja, Sanjana; Vashist, Sreshatha; Arisoyin, Abimbola; Bachu, Anil K.; Rajaram Manoharan, Senthil Vel Rajan; Mogallapu, Raja; Patel, Rikinkumar S. (Frontiers in Child and Adolescent Psychiatry, 2024)
Objective The aim of our study was to delineate the differences in demographics, comorbidities, and hospital outcomes by eating disorder types in adolescents and transitional-age youth (15–26 years), and measure the association with psychiatric comorbidities. Methods We conducted a cross-sectional study using the nationwide inpatient sample (2018–2019) and included 7,435 inpatients (age 12–24 years) with a primary diagnosis of eating disorders: anorexia nervosa (AN, 71.7%), bulimia nervosa (BN, 4.7%), avoidant/restrictive food intake disorder (ARFID, 9.5%), and other. We used independent logistic regression models controlled for demographics to evaluate the adjusted odds ratio association of comorbidities with eating disorder types. Results The mean age of BN inpatients was 17.5 years, which was significantly higher compared to the total number of inpatients with eating disorders (15.9 years). Approximately four-fifths of the inpatients with AN and BN were female patients whereas ARFID was seen in a higher proportion of male patients (32.6% vs. 13.7% overall). Anxiety (57.5%) and depressive (47.3%) disorders were prevalent in the total number of inpatients with eating disorders, with suicidal behaviors seen significantly higher in BN (25.7% vs. 12.9% overall). The likelihood of obsessive compulsive–related disorder was higher in all eating disorder types, i.e., AN (OR 2.14), BN (OR 1.79), and ARFID (OR 1.74); however, anxiety (OR 1.52) and neurodevelopmental (OR 1.70) disorders were significantly higher in ARFID. In terms of hospital outcomes, inpatients with ARFID had a longer mean length of stay (13.7 days vs. 8.4 days in BN) and higher mean total charges ($87,747 vs. $44,882 in BN). Conclusion Our findings identify notable demographic and clinical distinctions within inpatients diagnosed with AN, BN, and ARFID. Specifically, inpatients with BN belonging to older age brackets manifest elevated occurrences of depressive disorders and suicidal tendencies. ARFID is linked to prolonged hospitalization and increased costs, underscoring distinctive complexities in care. This highlights the significance of personalized interventions that account for demographic variations and psychiatric comorbidities, aiming to improve outcomes for diverse populations affected by eating disorders.